Small business sourcebook : the entrepreneur's resource - Darga, Amy (Small Business Sourcebook, 2003)
A two-volume annotated guide to 26,670 listings of live and print sources of information designed to facilitate the start-up, development, and growth of specific small businesses, as well as 26,158 similar listings for general small business topics. An additional 11,167 entries are provided on a state-by-state basis; also included are 965 relevant U.S. federal government agencies and branch offices.